First record of toxic Gymnodinium catenatum off'the west coast of Sabah Malaysia - Mohammad Noor, Normawaty; Adam, Aimimuliani; Franco Soler, J.M.; Anton, Ann; Muhammad Shaleh, Siti Raehanah (2008)
Gymnodinium catenatum, a toxic dinoflagellate was found to co-occurs in high cell densities with the bloom-forming Cochlodinium polykrikoides off the west coast of Sabah. maximum cell densities of G. catenatum recorded reached 1.24 x 105 cell/L, relative to C. polykrikoides densities of 1.54 x 107 cells/L. Gymnodinium catenatum forms long chains of up to 30 cells and is characterized by cells which are anterior-posteriorly compressed and with cell sizes ranging from 30-40 um. Toxicity studies based on RP-HPLC showed that this species produced PSP toxins. The occurrence of this species suggests increased PSP problems in addition to the presen of Pyrodinium bahamense var compressum, a PSP causing species in the west coast of Sabah